Clinical Features of Late-Onset Multiple Sclerosis: a Systematic Review and Meta-analysis - Naseri, Amirreza; Nasiri, Ehsan; Sahraian, Mohammad Ali; Daneshvar, Sara; Talebi, Mahnaz (Multiple sclerosis and related disorders, 2021)
•In about 5% of cases, Multiple sclerosis (MS) can be diagnosed at ages above 50 years old. Although the proportion of females is still more than males in Late-onset multiple sclerosis (LOMS); but there is a trend to increase in male cases with aging.•There is an increasing concern of a more progressive form of MS in LOMS cases. Also, we found a 65.00% proportion of spinal involvements in LOMS.•The most prevalent first disease presentation of LOMS is motor dysfunction followed by sensory problems, visual symptoms, and brainstem dysfunctions.•Understanding the proportion and clinical features of LOMS will help clinicians with the diagnosis of MS in this age group and prevention of wrong management plans and complications in these patients. Multiple sclerosis (MS) commonly affects young adults at the ages 20 to 40 years old, but it can onset at each age. Late-onset multiple sclerosis (LOMS) is defined as symptoms initiating after the age of 50. Misdiagnosis and a remarkable gap in diagnosis of LOMS is a challenge of the elderly population so in this article we described the proportion of LOMS and the clinical features and phenotype of the disease in this age group. After registration of the study protocol, an electronic search was performed in 3 databases and for full coverage of the published studies, we also checked the references of each related article. Two independent researchers screened the records in title/abstract and full-text stages and extracted the data using a data extraction table. The risk of bias was assessed using Joanna Briggs Institute checklist and meta-analysis was conducted by CMA 2. Only the studies with 50 years old cut-off and using McDonald or Poser diagnostic criteria were included in the meta-analysis. After removing duplicated studies, out of 733 results of electronic and hand searching, 31 studies met our inclusion criteria for the systematic review, and 11 of them were included in the quantitative synthesis. With different cut-offs and diagnostic methods 1.1% to 21.3% proportion of LOMS, has been reported in the studies. Meta-analysis reached a 5.01% (95% CI: 3.78% to 6.57%), proportion of LOMS in total MS cases. The female cases were more than males (range between 57.7% to 70.2%) and 64.46% (95% CI: 61.94% to 66.91%) proportion of females has been found in this study. 65.00% (95% CI: 44.71% to 81.02%) proportion of spinal cord involvements and 49.80% (95% CI: 39.28% to 60.24%) proportion of relapsing-remitting multiple sclerosis (RRMS) was also observed in LOMS cases. In 4 of included studies, the progressive form was the predominant phenotype. The most prevalent first disease presentation of LOMS was motor dysfunction (ranges between 100% to 35.4%) followed by sensory problems (ranges between 94% to 5%), visual symptoms (ranges between 22.9% to 5%), and brainstem dysfunction (ranges between 25% to 12.3%). The proportion of positive oligoclonal band (OCB), was varied from 46% to 98% in different studies and positive immunoglobulin G (IgG) index also was seen in 45.04% and 66% of the patients. 2.2% - 12.5% of the LOMS cases had a positive family history. In about 5% of cases, MS can be diagnosed at ages above 50 years old. There is an increasing concern of a more progressive form of MS in LOMS cases. Unlike the adult-onset MS, the first presentation of LOMS is usually motor dysfunction. Understanding the proportion and clinical features of LOMS will help clinicians with the diagnosis of MS in this age group and prevention of wrong management plans and complications in these patients. Although the proportion of females is still more than males in LOMS cases; but there is a trend to increase in male cases with aging.